How Has the Renminbi’s Role in Non-USD Currency Markets Evolved After COVID-19? An Analysis Based on Spillover Effects - Changrong Lu; Fandi Yu; Jiaxiang Li; Guanghong Zheng; Lian Liu (International Journal of Financial Studies)
Global uncertainty and the COVID-19 pandemic have significantly impacted the integration of emerging economies into global financial markets. Post-pandemic, the Federal Reserve’s interest rate hikes have drawn investor attention to relatively independent and stable currencies. This study investigates the sustained independence of the Renminbi by analyzing the spillover effects between the Renminbi and other major currencies in the context of the pandemic and USD interest rate hikes. By employing high-frequency data and cross-validating the results with low-frequency data transformed through Synchro Squeezing Wavelet Transform, we aimed to enhance the robustness of our findings. This analysis provides valuable insights for investors, highlighting the stability advantages of the Renminbi in the context of de-dollarization and global currency diversification.